The formation of an aesthetic taste as the most important component of art-pedagogical education (Pedagogy of Higher and Secondary Education, 2007)
The questions of formation of aesthetic taste as an important component of art-pedagogical education based on the main points of the monograph by N. Kalashnik «Aesthetic tastes: their cources andformation».
Keywords: aesthetical taste; esthetical feeling; esthetical ideal